Valorization of Lignocellulosic Waste (Crotalaria juncea) Using Alkaline Peroxide Pretreatment under Different Process Conditions: An Optimization Study on Separation of Lignin, Cellulose, and Hemicellulose. Issue 5 (4th July 2019) - Baksi, Sibashish; Saha, Sudeshna; Birgen, Cansu; Sarkar, Ujjaini; Preisig, Heinz A; Markussen, Sidsel; Wittgens, Bernd; Wentzel, Alexander
ABSTRACT: Lignocellulose materials, essentially consisting of lignin, cellulose and hemicelluloses, are abundant sources of fermentable sugars. The bast fiber of Crotalaria juncea ( Sunn hemp ), a native cover crop of India, was used as feedstock for this study. The primary objective of this study was to add value to the waste C. juncea bast fiber. The same was achieved by pretreating the waste fiber using alkaline peroxide solution at various process conditions. The optimal process condition for alkaline peroxide pretreatment was identified for the fiber to pretreatment solution (S/S) ratio of 1/40 at 50°C for 5h with respect to all response variables (lignin removal, hemicellulose recovery, recovery of solid pretreated material, and crystallinity of lignocellulose). Three-way ANOVA results revealed that S/S ratio had no significant effect; whereas, both temperature and time, and the combination of parameters, exhibited significant effect on response variables. The characteristic peaks associated with lignin and cellulose demonstrated a higher amount of lignin removal and increased cellulose content with elevated treatment time. Autoclave assisted pretreatment proved to be inefficient due to removal of lower amount of lignin in addition to higher hemicellulose degradation. On the other hand, pretreatment using ultrasound was found to be most effective in removing lignin, liberating hemicelluloses along with diminition in cellulose crystallinity.